Glutathione Transferase Response to Platinum Doped Titanium Dioxide in Aedes aegypti Pupae - Al-Salih, Moatasem; Al-Salih , Moatasem; Samsudin, Syakirah; Misnan, Rosmilah bt (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Aedes aegypti is a major vector of arboviruses, and increasing resistance to chemical insecticides demands novel control strategies. Specific Background: Photocatalytic nanoparticles such as Pt-doped TiO₂ generate reactive oxygen species under light, inducing oxidative injury in mosquitoes; however, the biochemical defense response, particularly glutathione S-transferase (GST), remains insufficiently understood at the pupal stage. Knowledge Gap: No study has simultaneously assessed lipid peroxidation and GST activity in Ae. aegypti pupae exposed to Pt-TiO₂ under different light conditions. Aims: This research examined malondialdehyde (MDA) levels and GST activity in pupae exposed to Pure TiO₂ and Pt-TiO₂ under light and dark conditions. Results: Light exposure significantly amplified oxidative stress and GST activity, with Pt-TiO₂ producing the highest MDA and strongest GST induction, while dark conditions showed no meaningful biochemical alterations. Novelty: The study provides the first integrated evidence linking enhanced photocatalytic ROS generation by Pt-TiO₂ to concurrent oxidative damage and compensatory antioxidant activation in pupae. Implications: These findings clarify the mechanism of Pt-TiO₂ toxicity and support its use as an efficient light-activated nano-insecticide for vector control.Highlight : Highlights the strong light-dependent oxidative stress induced by Pt-doped TiO₂ nanoparticles. Emphasizes GST upregulation as a key biochemical response to nanoparticle exposure. Shows that lipid peroxidation remains elevated despite antioxidant activation. Keywords : Aedes aegypti; Pt-doped TiO₂ nanoparticles; oxidative stress; glutathione S-transferase; malondialdehyde